Tumor Hypoxia as a Barrier in Cancer Therapy: Why Levels Matter - Hompland, Tord (Cancers (Basel), 2021)
SIMPLE SUMMARY: Hypoxia is a common feature of solid tumors and associated with poor outcome in most cancer types and treatment modalities, including radiotherapy, chemotherapy, surgery and, most likely, immunotherapy. Emerging strategies, such as proton therapy and combination therapies with radiation and hypoxia targeted drugs, provide new opportunities to overcome the hypoxia barrier and improve therapeutic outcome. Hypoxia is heterogeneously distributed both between and within tumors and shows large variations across patients not only in prevalence, but importantly, also in level. To best exploit the emerging strategies, a better understanding of how individual hypoxia levels from mild to severe affect tumor biology is vital. Here, we discuss our current knowledge on this topic and how we should proceed to gain more insight into the field. ABSTRACT: Hypoxia arises in tumor regions with insufficient oxygen supply and is a major barrier in cancer treatment. The distribution of hypoxia levels is highly heterogeneous, ranging from mild, almost non-hypoxic, to severe and anoxic levels. The individual hypoxia levels induce a variety of biological responses that impair the treatment effect. A stronger focus on hypoxia levels rather than the absence or presence of hypoxia in our investigations will help development of improved strategies to treat patients with hypoxic tumors. Current knowledge on how hypoxia levels are sensed by cancer cells and mediate cellular responses that promote treatment resistance is comprehensive. Recently, it has become evident that hypoxia also has an important, more unexplored role in the interaction between cancer cells, stroma and immune cells, influencing the composition and structure of the tumor microenvironment. Establishment of how such processes depend on the hypoxia level requires more advanced tumor models and methodology. In this review, we describe promising model systems and tools for investigations of hypoxia levels in tumors. We further present current knowledge and emerging research on cellular responses to individual levels, and discuss their impact in novel therapeutic approaches to overcome the hypoxia barrier.